Critical Plane Criterion for Fatigue Life Calculation: Time and Frequency Domain Formulations. (2015) - Carpinteri, Andrea; Spagnoli, Andrea; Ronchei, Camilla; Scorza, Daniela; Vantadori, Sabrina
Abstract: A frequency-domain critical plane criterion is here employed to estimate fatigue life of smooth metallic structural components under multiaxial random loading. The procedure set out in the present paper consists of the following three steps: (i) definition of the critical plane; (ii) PSD evaluation of an equivalent normal stress; (iii) determination of fatigue life. The criterion is theoretically developed and numerically validated by employing experimental fatigue results for structural steel subjected to combined bending and torsion.